2022
DOI: 10.1016/j.cell.2021.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Transition to invasive breast cancer is associated with progressive changes in the structure and composition of tumor stroma

Abstract: SUMMARY Ductal carcinoma in situ (DCIS) is a pre-invasive lesion that is thought to be a precursor to invasive breast cancer (IBC). To understand the changes in the tumor microenvironment (TME) accompanying transition to IBC, we used multiplexed ion beam imaging by time of flight (MIBI-TOF) and a 37-plex antibody staining panel to interrogate 79 clinically annotated surgical resections using machine learning tools for cell segmentation, pixel-based clustering, and object morph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
202
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(215 citation statements)
references
References 50 publications
11
202
1
1
Order By: Relevance
“…The mechanisms inducing the forces that myoepithelial cells exert on cancer cells of the luminal epithelial layer remain to be investigated. Most recently, morphometric quantifications comparing the myoepithelium of patients with ductal carcinoma in situ have shown that progressors have a thicker continuous myoepithelium [41], perhaps in response to aggressive luminal phenotypes. tumor.…”
Section: Trends In Cancermentioning
confidence: 99%
“…The mechanisms inducing the forces that myoepithelial cells exert on cancer cells of the luminal epithelial layer remain to be investigated. Most recently, morphometric quantifications comparing the myoepithelium of patients with ductal carcinoma in situ have shown that progressors have a thicker continuous myoepithelium [41], perhaps in response to aggressive luminal phenotypes. tumor.…”
Section: Trends In Cancermentioning
confidence: 99%
“…In addition, we observe many active marks both within the CDS, and 5’ to the 3UTR start (Figure S4A). As we were interested in the state of the cells in 2D organoids in relation to zonal SON 3UTR/CDS expression, we examined histone mark and other marker expression across the organoids, as a cellular measure of transcriptional activity (Risom et al, 2022; Vogelauer et al, 2000). Remarkably, most showed non-random, concentric expression in the 2D organoids (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study performed comparative profiling of DCIS epithelium and its microenvironment in samples from DCIS patients with or without subsequent invasive relapse (Risom et al, 2022). Their data indicated that patients with increased stromal cell infiltration, desmoplasia, and ECM remodeling were less likely to relapse to invasive disease (Risom et al, 2022). This study brings forward the intriguing notion of increased stromal desmoplasia correlating with a good prognosis in DCIS, contrary to its widely accepted role in tissue stiffening and cancer progression in IBC (Piersma et al, 2020; Schedin and Keely, 2011).…”
Section: Discussionmentioning
confidence: 99%